2018
DOI: 10.1007/s13361-018-2093-9
|View full text |Cite
|
Sign up to set email alerts
|

LC-MS/MS-Based Separation and Quantification of Marfey’s Reagent Derivatized Proteinogenic Amino Acid dl-Stereoisomers

Abstract: D-Amino acids are important biological molecules. Improved analytical methods for their resolution and quantification remain of keen interest. In this study, we investigated the use of Marfey's reagent (chiral) derivatization coupled with LC-MS/MS-based separation and detection of the resulting diastereomers for quantification of the 19 common L-and D-amino acids and glycine. Standard formic acid (pH 2) based separations on reverse phase media were unable to separate all 19 amino acid DL pairs. In contrast, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
58
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(59 citation statements)
references
References 40 publications
1
58
0
Order By: Relevance
“…L-Arg and Gly, present in the SCH peptaibols, were included among the derivatized standards for comparison but were absent from the samples, further confirming the differences among these compounds. It should be noted that relatively low absorbance for Aib and putrescine derivatives evident in chromatograms ( Figure S18 ) are likely due to slower derivatization reaction rates required for complete reaction with Marfey’s reagent [ 30 , 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…L-Arg and Gly, present in the SCH peptaibols, were included among the derivatized standards for comparison but were absent from the samples, further confirming the differences among these compounds. It should be noted that relatively low absorbance for Aib and putrescine derivatives evident in chromatograms ( Figure S18 ) are likely due to slower derivatization reaction rates required for complete reaction with Marfey’s reagent [ 30 , 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…In 1984, Marfey developed the N α -(5-Fluoro-2,4-dinitrophenyl)- l -alaninamide ( l -FDAA, also named Marfey’s reagent) enabling the indirect chiral resolution of amino acid enantiomers and successfully separated the diastereomeric l - and d -amino acids by HPLC [ 26 ]. This Marfey’s reagent is also compatible with LC/MS analysis [ 27 ]. Fujii et al reported an advanced Marfey’s reagent, N α -(5-Fluoro-2,4-dinitrophenyl)- l -leucinamide ( l -FDLA) [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the case of indirect approaches, with GC-MS, silylation agent such as N,O-Bis(trimethylsilyl)trifluoroacetamide (BSTFA) [22] or perfluorinated anhydrides [13] were used to obtain volatile derivatives prior to their separation in a CSP and (+)-α-methoxy-α-trifluoromethyl-phenylacetyl chloride to obtain diastereomeric amides [23]. In LC, it is common to use (R)-1-boc-2-piperidine carbonyl chloride [24]; ortho-phthalaldehyde (OPA)/ N-isobutyryl-L-cysteine (IBLC) reagent [25]; (R)-1-phenylethyl isothiocyanate ((R)-AMBI) [15], 1-fluoro-2,4-dinitrophenyl-5-L-alanine amide (Marfey´s reagent) [26,27]; 2,3,4,6-tetra-O-acetyl-beta-d-glucopyranosyl isothiocyanate (GITC); (S)-NIFE; 4-(3isothiocyanatopyrrolidin-1-yl)-7-nitrobenzofurazan (NBD-PyNCS) etc. [15,21] or homemade reactant as Biaryl Axially chiral derivatizing agent [28].…”
Section: Introductionmentioning
confidence: 99%